Private initiative in addressing fistula problem in Bangladesh - Akhter, Sayeba (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Fistula is a disease of the poorest women of poor country and treating fistula is always a non-profit venture. That is why private sector lags behind in the movement of fistula eradication. About 19,500 women are living with OF in Bangladesh. There is a rising trend in post-surgical fistula. Private initiatives also need to be encouraged and patronized for prevention and treatment of fistula. Methods: The purpose of this paper is to focus on the courageous attempt of running a fistula hospital in a private setup. MAMM’S Institute of Fistula & Women’s Health(MIFWOH) was established in 2012 in Dhaka, Bangladesh with an aim to serve the fistula victims of the country. Long term working experience in the field of genital tract fistula has facilitated the journey to a great extent. But challenges and obstacles are there. The purpose of this paper is to share the personal experiences of running a charitable hospital with private initiative. Results: The paper focuses on the success and challenges faced in past 5 years of journey. Around 1200 patients including 278 fistulae patients were treated during this period of time with an overall success rate of 86.33% in fistula surgery. The institute also takes initiative in training doctors and nurses for prevention and treatment of fistula. Challenges are there in respect of funding, space constrain, bringing patients to facility & also in developing surgical skills for taking over in future. Conclusions: Government and public participation is the dire necessity for future sustainability of the institute. At the same time focus must be put on encouraging young generation doctors in fistula surgery and train them up for future continuation of fistula eradication program.